Anoxygenic photosynthesis with emphasis on green sulfur bacteria and a perspective for hydrogen sulfide detoxification of anoxic environments - Kushkevych, Ivan; Procházka, Vít; Vítězová, Monika; Dordević, Dani; Abd El-Salam, Mohamed; Rittmann, Simon K.-M. R. (Frontiers in Microbiology, 2024)
The bacterial light-dependent energy metabolism can be divided into two types: oxygenic and anoxygenic photosynthesis. Bacterial oxygenic photosynthesis is similar to plants and is characteristic for cyanobacteria. Bacterial anoxygenic photosynthesis is performed by anoxygenic phototrophs, especially green sulfur bacteria (GSB; family Chlorobiaceae) and purple sulfur bacteria (PSB; family Chromatiaceae). In anoxygenic photosynthesis, hydrogen sulfide (H2S) is used as the main electron donor, which differs from plants or cyanobacteria where water is the main source of electrons. This review mainly focuses on the microbiology of GSB, which may be found in water or soil ecosystems where H2S is abundant. GSB oxidize H2S to elemental sulfur. GSB possess special structures – chlorosomes – wherein photosynthetic pigments are located. Chlorosomes are vesicles that are surrounded by a lipid monolayer that serve as light-collecting antennas. The carbon source of GSB is carbon dioxide which is assimilated through the reverse tricarboxylic acid cycle. Our review provides a thorough introduction to the comparative eco-physiology of GSB and discusses selected application possibilities of anoxygenic phototrophs in the fields of environmental management, bioremediation and biotechnology.